2018
DOI: 10.1105/tpc.17.00961
|View full text |Cite
|
Sign up to set email alerts
|

TEOSINTE BRANCHED1 Regulates Inflorescence Architecture and Development in Bread Wheat (Triticum aestivum)

Abstract: The flowers of major cereals are arranged on reproductive branches known as spikelets, which group together to form an inflorescence. Diversity for inflorescence architecture has been exploited during domestication to increase crop yields, and genetic variation for this trait has potential to further boost grain production. Multiple genes that regulate inflorescence architecture have been identified by studying alleles that modify gene activity or dosage; however, little is known in wheat. Here, we show () reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
223
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 212 publications
(232 citation statements)
references
References 87 publications
(152 reference statements)
4
223
1
4
Order By: Relevance
“…Wheat genotypes with higher than normal levels of TB1‐D1 expression have paired spikelets at each floret rather than a single spikelet due to extra branching. The extra branching is a result of delayed development of meristem identity tissue (Dixon et al ). Homoeologs of TB1 variants affecting spike architecture also exist in the A ( TB‐A1 ) and B ( TB‐B1 ) genomes, but variants of TB‐B1 seem to have a larger impact on spike architecture than TB‐A1 (Dixon et al ).…”
Section: Yield and Quality Genesmentioning
confidence: 99%
“…Wheat genotypes with higher than normal levels of TB1‐D1 expression have paired spikelets at each floret rather than a single spikelet due to extra branching. The extra branching is a result of delayed development of meristem identity tissue (Dixon et al ). Homoeologs of TB1 variants affecting spike architecture also exist in the A ( TB‐A1 ) and B ( TB‐B1 ) genomes, but variants of TB‐B1 seem to have a larger impact on spike architecture than TB‐A1 (Dixon et al ).…”
Section: Yield and Quality Genesmentioning
confidence: 99%
“…Moreover, FT‐B1 ( FT1 from the B genome of bread wheat) acts downstream of Ppd‐1 to influence spikelet number, with loss of FT‐B1 resulting in increased spikelet number, in a thermally‐responsive manner (Dixon et al ; Finnegan et al ) (Figure ). FT1‐dependent control of spikelet architecture was also supported by recent analysis of TEOSINTE BRANCHED1 ( TB1 ; orthologue of Vrs5 ) function in wheat, which facilitates paired spikelet development, in a dosage dependent manner, by interacting with FT1 and reducing FT1‐dependent activation of spikelet meristem identity genes (Dixon et al ) (Figure ). Investigation of plants that were tetrasomic for chromosome 4D and transgenic lines that expressed TB1 at higher levels showed that increased dosage of TB1 promotes paired spikelet development, and allelic variation for TB1 was shown to be associated significantly with paired spikelets in modern wheat cultivars (Dixon et al ).…”
Section: Beyond Domestication: a New Branch Of Understanding For Inflmentioning
confidence: 64%
“…FT1‐dependent control of spikelet architecture was also supported by recent analysis of TEOSINTE BRANCHED1 ( TB1 ; orthologue of Vrs5 ) function in wheat, which facilitates paired spikelet development, in a dosage dependent manner, by interacting with FT1 and reducing FT1‐dependent activation of spikelet meristem identity genes (Dixon et al ) (Figure ). Investigation of plants that were tetrasomic for chromosome 4D and transgenic lines that expressed TB1 at higher levels showed that increased dosage of TB1 promotes paired spikelet development, and allelic variation for TB1 was shown to be associated significantly with paired spikelets in modern wheat cultivars (Dixon et al ). Taken together, these results show that transcriptional and post‐translational regulation of flowering signals can alter inflorescence architecture, which has potential to be used as a mechanism for increasing spikelet and floret numbers in wheat.…”
Section: Beyond Domestication: a New Branch Of Understanding For Inflmentioning
confidence: 64%
See 2 more Smart Citations